The Amount of Water used to Wash Hands to Prevent The Spread of Covid-19 - Fitriati, Ulfa; Wardhana, Henry; Ma'ruf, Muhammad Afief; Hidayatullah, Fiki (Fakultas Teknik Universitas Brawijaya, 2024)
Based on the WHO data updated on December 28, 2021, the global tally of COVID-19 cases for that year reached 281,808,270, with a reported 5,411,759 deaths worldwide. Specifically in Indonesia, the cases total 5,411,759, with 144,081 deaths by that date. To reduce the risk of transmission, practicing good hand hygiene is crucial. Regular hand washing with soap and water or using an alcohol-based hand sanitizer when soap isn't available helps remove pathogens from our hands, contributing to a cleaner and healthier lifestyle. Collecting rainwater in specially designed containers can be an effective and sustainable way to meet handwashing needs, supporting health protocols to prevent the spread of COVID-19. By providing an accessible water source for hand hygiene, communities, especially those with limited water access, can implement handwashing practices more consistently. This initiative is beneficial for promoting both environmental sustainability and public health, particularly in areas facing water scarcity. Additionally, filtration or disinfection processes can enhance rainwater collection systems to ensure safe water for handwashing, further supporting a cleaner and healthier environment. The result is that visitors wash their hands on average 5 times per day, with an average volume of 0.6 liters of water used in a one-time hand wash. With an interval of 6 days without rain, the maximum hand washing needs are 53.35 m3. The roof area in the market is 16,240 m2, and the water volume from effective rain is 21.11 m3. If we use a reservoir of 1200 liters, we need 22 22-unit reservoirs for maximum water demand.